Integrating Financial Literacy and Digital Marketing for Craft Msmes in Aceh: Strategic Initiatives for Business Sustainability - Mariana Mariana; Yudhy Widya Kusumo; Muhammad Muhammad; Karnita Sartina; A’zizah A’zizah; Yusriadi Yusriadi (TAAWUN, 2025)
The aim of this research is to improve the financial management skills of small and medium-sized enterprises (SMEs) in the craft sector in Aceh Province through training that focuses on separating personal and business finances, proper transaction recording, and the preparation of transparent and accurate financial reports. The method used in this community service activity involves training conducted by a team of lecturers from various educational institutions, as well as direct visits to SME locations for practical training. The results show that most SME owners previously lacked adequate understanding of financial management, and this training provided significant benefits in enhancing their ability to make better business decisions. The Focus Group Discussion (FGD) revealed challenges faced by SMEs, such as limited capital and difficulties in product marketing. In conclusion, this financial management training has had a positive impact on SME owners in Aceh, helping them develop a more professional and sustainable approach to business operations. Notably, this program stands out as the first to integrate simple app-based financial management training with digital marketing strategies in Aceh. By combining financial literacy with modern marketing techniques, the program provides a comprehensive solution for the challenges faced by local MSMEs. Integrating these two crucial aspects empowers business owners to manage their finances better while expanding their market reach through digital platforms. This innovative approach lays the groundwork for more resilient and competitive MSMEs, fostering long-term sustainability and growth in the region.